{2-[(1,3-Benzothiazol-2-yl)methoxy]-5-chlorophenyl}(4-chlorophenyl)methanone - K. N. Venugopala; Susanta K. Nayak; B. Odhav (Acta Crystallographica Section E, 2013)
In the title compound, C21H13Cl2NO2S, the benzothiazole ring makes dihedral angles of 0.94 (1) and 70.65 (5)° with the 4-chlorophenylmethanone unit and the 5-chlorophenyl ring, respectively. The dihedral angle between the 4-chlorophenylmethanone unit and the 5-chlorophenyl ring is 66.20 (5)°. The crystal structure consists of dimeric units generated by C—H...N hydrogen bonds, further linked by C—H...O and C—H...π interactions, leading to a three-dimensional network.